Myeloid Cell-Derived Arginase in Cancer Immune Response - Grzywa, Tomasz M.; Sosnowska, Anna; Matryba, Paweł; Rydzynska, Zuzanna; Jasinski, Marcin; Nowis, Dominika; Golab, Jakub (Frontiers in Immunology, 2020)
Amino acid metabolism is a critical regulator of the immune response, and its modulating becomes a promising approach in various forms of immunotherapy. Insufficient concentrations of essential amino acids restrict T-cells activation and proliferation. However, only arginases, that degrade ʟ-arginine, as well as enzymes that hydrolyze ʟ-tryptophan are substantially increased in cancer. Two arginase isoforms, ARG1 and ARG2, have been found to be present in tumors and their increased activity usually correlates with more advanced disease and worse clinical prognosis. Nearly all types of myeloid cells were reported to produce arginases and the increased numbers of various populations of myeloid-derived suppressor cells and macrophages correlate with inferior clinical outcomes of cancer patients. Here, we describe the role of arginases produced by myeloid cells in regulating various populations of immune cells, discuss molecular mechanisms of immunoregulatory processes involving ʟ-arginine metabolism and outline therapeutic approaches to mitigate the negative effects of arginases on antitumor immune response. Development of potent arginase inhibitors, with improved pharmacokinetic properties, may lead to the development of novel therapeutic strategies based on targeting immunoregulatory pathways controlled by ʟ-arginine degradation.